Comparative Study of the Infestation of Namchi (Bos taurus) and Ngaoundere Gudali (Bos indicus) Cattle by Amblyommavariegatum Adult Ticks - M. D. Achukwi; V. N. Tanya; O. Messiné; L. M. Njongmeta (Revue d’Elevage et de Médecine Vétérinaire des Pays Tropicaux, 2001)
The relative attraction of Amblyomma variegatum adult  ticks for Namchi (Bos taurus) and Ngaoundere Gudali (Bos indicus) cattle was assessed during natural infestation on pasture. The adult ticks were counted once a week for six weeks. The method of analysis of variance (ANOVA) with repeated data and the generalized  linear models (GLIM) showed variations in the animal infestation. Adult ticks were less attracted to Namchi than to Gudali cattle (P < 0.05). The infestation ratesalso varied with time and the infestation site on the animal (P < 0.05): the umbilical-genital area was the most infested,where as ears, back and rump were the least. Results seemed to indicate a natural resistance of Namchi cattle to A.variegatum. This in born capacity of Namchi cattle to attract fewer ticks could be used to implement a sustainable and environment-friendly control strategy.